1996
DOI: 10.1046/j.1365-2958.1996.00061.x
|View full text |Cite
|
Sign up to set email alerts
|

A cyclophilin‐like peptidyl‐prolyl cis/trans isomerase from Legionella pneumophila – characterization, molecular cloning and overexpression

Abstract: Legionella pneumophila is the causative agent of a severe form of pneumonia in humans (Legionnaires' disease). A major virulence factor, the Mip protein (FK506-binding protein, FKBP25mem), belongs to the enzyme family of peptidyl-prolyl cis/trans isomerases (PPlases). Here we show that L. pneumophila Philadelphia I possesses an additional cytoplasmic PPlase at a level of enzyme activity comparable to that of FKBP25mem. The N-terminal amino acid sequence of the purified protein was obtained by Edman degradation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
29
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 72 publications
3
29
0
Order By: Relevance
“…1, center panel, lane H). A previous report showed that, at least for the L. pneumophila LpCyp18 cyclophilin, the hypothetical associated nuclease activity was not linked with its native structure (12). These results are coherent with our find-ing that the nuclease activity is caused by a different protein.…”
supporting
confidence: 92%
See 3 more Smart Citations
“…1, center panel, lane H). A previous report showed that, at least for the L. pneumophila LpCyp18 cyclophilin, the hypothetical associated nuclease activity was not linked with its native structure (12). These results are coherent with our find-ing that the nuclease activity is caused by a different protein.…”
supporting
confidence: 92%
“…Some reports on human recombinant CypA, CypB, and CypC cyclophilins (6), murine CypB cyclophilin (8), Legionella pneumophila LpCyp18 cyclophilin (12), and Streptomyces antibioticus-SanCyp18 cyclophilin (9) describe associated Ca 2ϩ / Mg 2ϩ nuclease-dependent activity. For the aforementioned eukaryotic cyclophilins, the accompanying nuclease activity has been proposed as playing a central role in apoptosis.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Legionella also possess a second cytoplasmic cyclophilin, cyclophilin 18. Mip protein is not necessary for the extracellular survival of Legionella, but disruption mutants are 10 times less invasive of Acanthamoeba castellani (20). Interestingly, the Hc CypA sequence is not homologous to L. pneumophila Mip, but shows a high degree of conservation with the cytoplasmic form cyclophilin 18.…”
Section: Discussionmentioning
confidence: 99%